Synthesis of Iron Oxide Nanoparticles by Chemical Precipitation Method and Study of Their Structural, Morphological, and Biological Properties - Ghanem Kazem (Journal of Health and Biology, 2026)
Iron oxide nanoparticles (Fe2O3 NPs) were successfully produced by a simple precipitation method using ferric chloride (FeCl3.6H2O) and ferrous sulphate (FeSO4.7H2O) in an alkaline medium. The lattice structure, morphology, and surface properties of the produced nanoparticles were studied by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Atomic force microscopy (AFM) was used. The XRD study validated the synthesis of pure a-Fe2O3 (hematite) phases with an average crystalline grain size of ~28.4 nm calculated by the Scherrer equation. The SEM scans revealed compact quasicrystalline particles with a rather narrow size distribution in the range of 20-40 nm. The AFM observations provided the surface topography data at the nanoscale with a radical RMS of 3.7 nm. Biological studies: Antibacterial activity by the disc diffusion method against four important clinical pathogens (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumonia). The inhibition of growth up to 22 mm at 100 µg /ml of nanoparticles showed a robust antibacterial activity. The MTT assay revealed dose-dependent cytotoxicity against the MCF-7 breast cancer cell line with an IC50 value of 45.3 µg/mL. The results indicate that the chemically produced Fe2O3 nanoparticles are extremely promising for possible use in biomedical applications such as cancer therapy and medication delivery.